(untitled) (Journal of the College of Basic Education, 2023)
Comedy enjoys wide public acceptance and is affected by great interest, mostly due to the nature of the characteristics of internal comedy, the power of attraction and influence that it involves, in addition to the multiplicity of functions it performs and its ability to respond to the requirements of the psychological need of the audience. So the(Quickness of intuition and the ability to adapt to the event is one of the most important characteristics of the comedian. The lack of consistency and organization may spoil the pleasure of reception or the viewer. Actor Charlie Chaplin believes that the excitement of expectation and its absence may be considered one of the most important artistic elements that effectively prepare the atmosphere and mood for what is presented. comic acts for the viewer).And if the success of the dramatic work in general is based on the interaction of a number of basic elements that complement each other, then it can be claimed that the actor occupies the leading position among these elements in comedies. And there is an important feature of the comedy is that it (depends in its success on the indifference of the spectators and the lack of emotional indulgence harmful to the comic spirit.Every comedian has his own style of performance that distinguishes him from other actors, and this style must be reflected in his work. It can be known as a sense of comedy, which is based on new elements in which spontaniety blends with the spirit of humor and the ability to improvise as well as muscle flexibility, which facilitates control of facial features in particular and expression in movement in addition to the voice. Therefore, (the task of the actor is to work on interrogating the character and inventing means of expression, and he is not satisfied with what he achieved in the first performance. Rather, there is always a new discovery, addition and innovation within the fabric of the theatrical performance. The performance continues continuously and is not satisfied with the data of the rehearsal time. The recipient is renewed and the theatrical space changes and matures within the time and place of the performance. the play itself). ( )